2013
DOI: 10.1080/10570314.2013.770161
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Jealousy and Relationship Satisfaction: The Costs of Rumination

Abstract: The experience of romantic jealousy and its influence on relationship outcomes is unclear. Romantic jealousy is often associated with damaging effects; on the other hand, jealousy is linked to positive relationship outcomes such as increased commitment. In this study, we aimed to address inconsistencies in previous research by proposing rumination as a mediator between romantic jealousy (cognitive jealousy and surveillance behaviors) and relationship dissatisfaction. We also aimed to extend our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 36 publications
(47 reference statements)
2
28
1
Order By: Relevance
“…Difficulty in handling jealousy was also observed in the acceptance and no-threats versus threats categories. This helps to explain the finding that, when compared with the general population, only participants in the P Group indicated problems stemming out from jealousy, an aspect that has already been discussed by other scholars (Dossi et al, 2008;Elphinston et al, 2013). Thus, it can be inferred that the jealous behavior regarding the partner has an impact on the anxiety levels among the perpetrators, which are associated with the emergence of cognitive patterns indicative of jealousy, such as distrust, and the need to control and surveil which result in psychological aggression that precedes episodes of physical violence (Buss, 2000;Doğan, 2016;Pavela et al, 2014).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Difficulty in handling jealousy was also observed in the acceptance and no-threats versus threats categories. This helps to explain the finding that, when compared with the general population, only participants in the P Group indicated problems stemming out from jealousy, an aspect that has already been discussed by other scholars (Dossi et al, 2008;Elphinston et al, 2013). Thus, it can be inferred that the jealous behavior regarding the partner has an impact on the anxiety levels among the perpetrators, which are associated with the emergence of cognitive patterns indicative of jealousy, such as distrust, and the need to control and surveil which result in psychological aggression that precedes episodes of physical violence (Buss, 2000;Doğan, 2016;Pavela et al, 2014).…”
Section: Discussionsupporting
confidence: 53%
“…Jealousy in romantic relationships is present in all societies and cultures and it involves a set of complex cognitive, emotional, physiological, and behavioral responses determined by a perceived threat to an intimate relationship by a rival, regardless of whether that threat is real or not (Elphinston, Feeney, Noller, Connor, & Fitzgerald, 2013;Gouveia, Silveira, Santos, Souza, & Belo, 2015;Pavela, Banai, & Šimic, 2014;Ramos, Yazawa, & Salazar, 1994). The diversity of such responses can be observed through the set of feelings associated with jealousy, such as anger, fear, sadness, excessive distrust, and may be accompanied by aggressive behavior (Buss, 2000;Doğan, 2016;Elphinston et al, 2013;Wigman, Graham-Kevan & Archer, 2008). Research shows that jealousy is a heterogeneous condition ranging from normal to pathological, with different degrees and levels of persistence manifested over time (Marazziti et al, 2010;Ramos, et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sidelinger and Booth-Butterfield (2007) found that relationship satisfaction was negatively related to cognitive jealousy but was unrelated to emotional jealousy. Finally, Elphinston, Feeney, Noller, Connor, and Fitzgerald (2013) found both behavioral and cognitive jealousy to be positively associated with relationship dissatisfaction. Overall, two paths to relationship dissatisfaction emerged.…”
Section: Jealousymentioning
confidence: 92%
“…Therefore, we speculate that it is a lover’s betrayal that causes anger and other negative emotions, resulting in hate. Moreover, cognitive jealousy is directly related to relationship dissatisfaction between lovers ( Elphinston et al, 2013 ). Previous studies have also found a positive relationship between romantic love and jealousy.…”
Section: Discussionmentioning
confidence: 99%